Implication of problematic substance use in poststroke depression: an hospital-based study - Yolaine Rabat; Igor Sibon; Sylvie Berthoz (Scientific Reports, 2021)
Abstract The prevalence of clinically defined problematic substance use among stroke patients is overlooked and its association with post-stroke depression (PSD) is unknown. Our aims were to: (1) estimate the proportion of stroke patients with a problematic substance use as defined by clinical screening scales; (2) determine the proportion of PSD at three months of follow-up; (3) explore if the baseline severity in substance use and its evolution are independent predictors of PSD. A cohort of first-ever non-severe stroke adult patients was screened at baseline and three months post-stroke using recommended cut-off scores of standardized scales for tobacco, alcohol and cannabis abuse. PSD was defined using the Center of Epidemiological Studies Depression scale score. Out of the 244 eligible patients, 74 (30.3%) presented a problematic substance use, including 21 (8.6%) polydrug abusers. Among these patients, the prevalence of PSD was 50.8%, including 29.5% of severe depression. The severity of tobacco dependence at baseline was found to double the risk (OR 1.59, 95% CI 1.05–2.43) of presenting a PSD, independently of previously reported risk factors. We found no significant evidence for an effect of the evolution in substance use at follow-up. Addictive disorders are part of the critical unmet needs that should be addressed in the management of PSD.